2020
DOI: 10.1016/j.heliyon.2020.e04505
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variations in Bi2S3 nanoparticles synthesized by using a single source precursor

Abstract: A simple solvothermal decomposition of bismuth dithiocarbamate complex in oleylamine, oleic acid, and hexadecylamine at 180 °C, yielded bismuth sulphide nanomaterials of different morphologies represented as Bi 2 S 3 (OAm), Bi 2 S 3 (OAc) and Bi 2 S 3 (HDA) respectively. The bismuth complex, used as the single source precursor, was synthesized and characterised by elemental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Bismuth dithiocarbamate was the Bi source in that work. 232 This journal is © The Royal Society of Chemistry 2022 Nanoscale Horiz., 2022, 7, 941-1015 | 975…”
Section: Miscellaneous Metal Chalcogenidesmentioning
confidence: 99%
“…Bismuth dithiocarbamate was the Bi source in that work. 232 This journal is © The Royal Society of Chemistry 2022 Nanoscale Horiz., 2022, 7, 941-1015 | 975…”
Section: Miscellaneous Metal Chalcogenidesmentioning
confidence: 99%
“…2e and f ) NRs implied that the weight percentages of Bi and S decreased from 78.2% and 21.8% to 77.0% and 17.7%, respectively, after HA coating. 64 We also found that O (1.1%) and N (0.1%) elements were present in BiH NRs, indicating the successful introduction of HA to the surface of Bi 2 S 3 NRs. In addition, UV-Vis spectra of both Bi 2 S 3 and BiH NRs showed an obvious absorption at 808 nm, indicating their potential to be photothermal agents (Fig.…”
Section: Biomaterials Science Papermentioning
confidence: 52%
“…However, adding La increased the intensity of the (211) plane of Bi 2 S 3 at the diffraction peak 2 = 28:65 °. It indicated the bias of orientations of these crystallographic planes [29]. The 211 facets were the most dominant in Bi 2 S 3, suggesting the formation of microsphere 5 Journal of Nanomaterials particles [30].…”
Section: Photocatalytic Degradationmentioning
confidence: 97%